Influence Small Sided Games and Wall Passes Against Ability Passing Athlete Age 15-17 Years SSB Putra Sampantao - Nono Hardinoto; Elvin Harungguan Pasaribu; Mahmuddin Mahmuddin; Asep Prima (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Football is a sport that is growing rapidly and is popular throughout the world, both in society, schools and workplaces as evidenced by the growing number of football clubs. The basic skills of playing soccer are very important to apply in improving the ability to play soccer. One of the basic skills in football is passing ability which can be improved with Small Sided Games and Wall Pass exercises. This study aims to determine the significant effect of Small Sided Games and Wall Pass exercises on Passing ability in football games aged 15-17 years SBB Putra Sampatao Sei Mangkei Simalungun Regency in 1011. This research is an experimental study with a pretest and posttest design one group design. The sample in the study was 11 SSB Putra Sampatao Sei Mangkei athletes aged 15-17 years. After the pretest was carried out, the sample was then given small sided games and wall pass exercises for 18 meetings (6 weeks). The data analysis technique in this study used the t test. Based on the results of statistical tests using the t-test with a significant level (α = 0.05) between the pre-test and post-test of passing ability, the value of tcount 10.141 > ttable 1.811 means that Ho is rejected and Ha is accepted. The conclusion of this study is that there is a significant effect of small sided games and wall pass exercises on passing ability in soccer games aged 15-17 years SSB Putra Sampatao Sei Mangkei Simalungun Regency in 1011.